Review of Current Concepts: Greater Trochanteric Pain Syndrome - Márquez Arabia, William Henry; Gómez-Hoyos, Juan; Llano, Juan Fernando (Revista Colombiana de Ortopedia y Traumatología, 2013)
Lateral hip pain often becomes a challenging diagnostic and therapeutic problem. As there are a number of differential diagnoses that should be taken into account, this implies that there is a group of signs and symptoms related to greater trochanteric pain, and may be more complex than a simple inflammation of the trochanteric bursae. Around 2.5% of sports injuries involve the hip, and greater trochanteric pain has been estimated at 1.8 per 1000 patients per year. This condition occurs in adults, with the highest prevalence between the fourth and sixth decades of life. The specific diagnosis of the greater trochanteric pain syndrome include trochanteric bursitis, external snapping hip (external coxa saltans), and ruptures of the tendons of the gluteus medius and lower gluteus. We present a review of the scientific literature that enables the reader to make an adequate differential diagnosis between the above-mentioned pathologies.